Regulation of the reproductive cycle and early pregnancy by relaxin family peptides - Anand-Ivell, Ravinder; Ivell, Richard (Elsevier, 2014)
The relaxin family of peptide hormones are structurally closely related to one another sharing a heterodimeric A–B structure, like that of insulin. They may also be active as unprocessed B–C–A pro-forms. Relaxin has been shown to pay a key role within the ovary, being involved in follicle growth, and ovulation. Relaxin is produced in large amounts also by the corpus luteum where it acts as an endocrine hormone positively affecting implantation, placentation and vascularization during the all-important first trimester phase of pregnancy establishment. Relaxin exerts its functions via the receptor RXFP1. Insulin-like peptide 3 (INSL3) in contrast acts through the related receptor RXFP2, and plays an essential role in the production of androgens within growing antral follicles. INSL3 is also produced in large amounts by the male fetus shortly after sex determination, where it controls the first transabdominal phase of testicular descent. However, this fetal INSL3 is also able to influence placental and maternal physiology, indicating associations with later preeclampsia and/or fetal growth restriction. Other members of this relaxin-like family of peptides, such as INSL4, INSL5 and INSL6 are less well studied, though all suggest modulatory roles in ovarian and/or placental function.